Pelatihan Pengembangan Pengolahan Bandeng Presto Desa Blendung Kec.Ulujami, Kab.Pemalang - Sukardi Sukardi; Turkhamun Turkhamun; Deewar Mahesa (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The village of Blendung, located in the Ulujami sub-district, Pemalang Regency, faces various social and economic challenges, including high unemployment rates and declining incomes due to limited job access and the impact of tidal flooding. One of the efforts to increase community income is through training in making presto milkfish, aimed at empowering Micro, Small, and Medium Enterprises (MSMEs) in the fish processing sector. This training is designed to enhance community skills in diversifying milkfish-based products, such as boneless milkfish, fish cakes, and smoked milkfish, as well as introducing digital marketing strategies to expand the market.The methods used include a participatory approach in processing and packaging technology training, as well as social media-based marketing education. The results of the training showed an improvement in the skills and understanding of participants regarding the production and marketing processes of value-added products. This program also contributes to the growth of local MSMEs, which have significant potential in supporting the regional economy.